Prophylactic significance of Karnapichu in electronic sound device induced ear diseases: A conceptual Study - Sheenam, V D; fiaz, Shamsa (International Research Journal of Ayurveda & Yoga, 2020)
In present era use of electronic sound devices increased dramatically. Mobile, headphones, earphones, neckbands, are the common devices use to enhance the sound experience. Over use of these devices leads to impairment of hearing, tinnitus, otalgia and many other ear diseases. Ayurveda has a strong prophylactic protocol to every disease. By following this human being can prevent himself from many diseases. Karnapichu is a procedure where cotton wick dipped in lukewarm medicated oil is inserted into the external auditory canal which nourishes the acoustic nerve and improves the signal quality to brain. Karnapichu is easy procedure in comparison to others so it can be easily used by the common man suffering such problems on day to day basis. Which helps to prevent electronic sound device induced ear diseases.